Influence of environmental factors on the germination of Urena lobata L. and its response to herbicides - Awan, Tahir Hussain; Chauhan, Bhagirath Singh; Sta. Cruz, Pompe C. (Public Library of Science, 2014)
Urena lobata is becoming a noxious and invasive weed in rangelands, pastures, and undisturbed areas in the Philippines. This study determined the effects of seed scarification, light, salt and water stress, amount of rice residue, and seed burial depth on seed germination and emergence of U. lobata; and evaluated the weed's response to post-emergence herbicides. Germination was stimulated by both mechanical and chemical seed scarifications. The combination of the two scarification methods provided maximum (99%) seed germination. Germination was slightly stimulated when seeds were placed in light (65%) compared with when seeds were kept in the dark (46%). Sodium chloride concentrations ranging from 0 to 200 mM and osmotic potential ranging from 0 to −1.6 MPa affected the germination of U. lobata seeds significantly. The osmotic potential required for 50% inhibition of the maximum germination was −0.1 MPa; however, some seeds germinated at −0.8 MPa, but none germinated at −1.6 MPa. Seedling emergence and biomass increased with increase in rice residue amount up to 4 t ha−1, but declined beyond this amount. Soil surface placement of weed seeds resulted in the highest seedling emergence (84%), which declined with increase in burial depth. The burial depth required for 50% inhibition of maximum emergence was 2 cm; emergence was greatly reduced (93%) at burial depth of 4 cm or more. Weed seedling biomass also decreased with increase in burial depth. Bispyribac-sodium, a commonly used herbicide in rice, sprayed at the 4-leaf stage of the weed, provided 100% control, which did not differ much with 2,4-D (98%), glyphosate (97%), and thiobencarb + 2,4-D (98%). These herbicides reduced shoot and root biomass by 99–100%.